2012
DOI: 10.1152/ajplung.00050.2011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a sphingosine-1-phosphate analog inhibits airway remodeling following repeated allergen exposure

Abstract: Sphingosine-1-phosphate (S1P) is an immunomodulatory lipid mediator that plays an important role in lymphocyte trafficking. Elevated levels of S1P are found in bronchoalveolar lavage (BAL) fluid of patients with asthma; however, its role in disease is not known. FTY720, a synthetic analog of S1P, has been shown to abrogate allergic inflammation and airway hyperresponsiveness following acute allergen challenge. However, its effects on asthmatic airway remodeling induced by repeated allergen exposure are unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…Although our sensitization regimen differed somewhat from the work of others, the range of hyperresponsiveness seen after 3 wks sensitization was comparable to that previously reported in the Brown Norway rat after HDM sensitization [12,31]. Furthermore, baseline airway resistance and the level of reactivity after allergen sensitization was similar to that observed by Karmouty-Quintana who showed concomitant increases in airway vascularity after ovalbumin sensitization [13]. …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although our sensitization regimen differed somewhat from the work of others, the range of hyperresponsiveness seen after 3 wks sensitization was comparable to that previously reported in the Brown Norway rat after HDM sensitization [12,31]. Furthermore, baseline airway resistance and the level of reactivity after allergen sensitization was similar to that observed by Karmouty-Quintana who showed concomitant increases in airway vascularity after ovalbumin sensitization [13]. …”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, several studies have shown that allergen sensitization leads to increased airway vascularity concomitant with enhanced reactivity and inflammation [13,27]. Both ovalbumin and house dust mite have been used to sensitize mice where investigators have reported increased lung vascularity of relatively large pulmonary vessels associated with large airways [8,9,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The U.S. BN rats also fail to develop AHR (19). We have previously observed differences in the degree of vascular remodeling and inflammation and of expression in Th2 cytokines between U.S. and UK BN rats (15,47). Previous studies of allergen-challenged BN rats have shown that increased ASM mass is attributable to hyperplasia (31,34,45).…”
Section: Discussionmentioning
confidence: 85%